High-Risk Human Papillomavirus DNA Test: Could It Be Useful in Low-Grade Cervical Lesion Triage? Five-Year Follow-Up. (February 2014) - Saccardi, Carlo; Gizzo, Salvatore; Noventa, Marco; Anis, Omar; Gangi, Stefania Di; Patrelli, Tito Silvio; D'Antona, Donato; Nardelli, Giovanni Battista
We conducted a retrospective, observational study in order to evaluate the role of high-risk human papillomavirus (hrHPV)-DNA test in patients with first diagnosis of low-grade squamous intraepithelial lesions (L-SILs).Patients were divided into group A, annual Papanicolaou test and hrHPV-DNA tests (167 patients) and group B, immediate colposcopy, followed by annual papanicolaou test and hrHPV-DNA tests (164 patients). We assessed sensitivity, specificity, negative predictive value (NPV), positive predictive value, positive–negative likelihood ratio of hrHPV-DNA test, and 5-year relative risk of cervical intraepithelial neoplasia grade 2 in hrHPV-DNA+. Colposcopy is still considered the best choice for women with L-SIL and hrHPV-DNA+ test. High sensitivity and NPV of hrHPV-DNA test permit to use it in the follow-up of L-SIL with a HPV-negative status, without necessity of referring to colposcopy.